Women and Sufism: Perspectives on History, Gender, and the Contemporary Application of Maqāṣid al-Sharīʿah - Tandos, Rosita; Kuba, Amiruddin (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
This article examines the role of women in Sufism from the perspective of Islamic law, focusing on their spiritual practices, historical contributions, and contemporary relevance. It employs a qualitative interpretive approach, drawing on literature analysis, observations of online Sufi learning activities, and semi-structured interviews with women participating in Sufi study circles. The analysis is grounded in Jasser Auda’s Maqāṣid al-Sharīʿah framework, through which women’s spiritual engagement is assessed in relation to key legal objectives, including the preservation of religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), lineage (ḥifẓ al-nasl), and human dignity (ḥifẓ al-karāmah al-insāniyyah). The findings demonstrate that Sufi teachings, which emphasize spiritual equality and inner transformation, provide a normative Islamic basis for women’s active participation as spiritual leaders, intellectuals, and social actors. The study contributes to Islamic legal discourse by showing that women’s engagement in Sufism represents a viable and internally grounded framework for advancing gender equity and holistic human well-being within the tradition.